Krall. Weaving - Roszak, Joanna (Lodz University Press, 2024)
The book Krall. Weaving I present, how Krall collects the shards of a mirror, not only Andersen’s one, which infects with evil, but also – simply – Stendhal’s one (if a novel is like a mirror carried along a high road, even more so is a reportage). The author takes readers to the other side of the mirror: she forages for additional dimensions in her texts, a more advanced description of reality or a new perspective. What visibly emerges from Hanna Krall’s latest book is a pattern of strong interlacing. The two artistic processes that organize her texts are still collage (of stories, an attempt to determine them after the mirror breaks, from photos, prints) and montage (as a process of combining them into a coherent whole, possibly with a narrative designed to be incoherent). I am interested in Hanna Krall’s (auto)biographical experience and its (non)presence in her writing. Hanna Krall’s experience is obviously Jewish, although she has consistently kept silent about her own family history, and has not developed it in the form of a reportage in more detail and open way than in the text I mentioned above. Nevertheless, from the interview conducted by Wojciech Tochman we know a lot of precious details. I imagined the first part of the book as an attempt to put together a family history – from textual and non-textual scraps. In the concluding chapter, The Sa-crall-ization of the Storytelling I notice the act of writing as saving memory. Some of Krall’s texts catty a trace of exhaustion and amnesia. At the dedication ceremony of the United States Holocaust Memorial Museum in Washington on April 22, 1993, Elie Wiesel reiterated: “This museum is not an answer, it is a question mark”. Just as Hanna Krall’s opus is.